2021
DOI: 10.32800/abc.2022.45.0043
|View full text |Cite
|
Sign up to set email alerts
|

New records of leeches of the genus Limnatis (Hirudinea, Praobdellidae) from the South Caucasus and Central Asia: phylogenetic relationships of Eurasian and African populations

Abstract: Leeches of the genus Limnatis Moquin–Tandon, 1827 infest mucous membranes of various mammals, including humans and domestic ungulates. The type species of the genus L. nilotica (Savigny, 1822) was initially thought to occur throughout the Western Palaearctic, from North Africa to the Middle East and Central Asia. It was later found that L. paluda (Tennent, 1859) is a widespread Western Asian species. However, the South Caucasus and vast areas of Central Asia have not been explored sufficiently in terms of leec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(21 reference statements)
1
2
0
Order By: Relevance
“…Likewise, it was also observed that it was larger than the L. paluda species determined from Kazakhstan [15] and other regions in Central Asia [6, 16, and 17]. While the samples of L. paluda determined in Ceylon (Sri Lanka), India, and Saudi Arabia region [11 and 24] were smaller than the samples in our study, it was observed that the species determined from Iran [19] were almost similar in size. It should be noted that the size of leeches increases after feeding, but it is not a mistake to conclude based on the materials.…”
Section: Methodssupporting
confidence: 59%
See 2 more Smart Citations
“…Likewise, it was also observed that it was larger than the L. paluda species determined from Kazakhstan [15] and other regions in Central Asia [6, 16, and 17]. While the samples of L. paluda determined in Ceylon (Sri Lanka), India, and Saudi Arabia region [11 and 24] were smaller than the samples in our study, it was observed that the species determined from Iran [19] were almost similar in size. It should be noted that the size of leeches increases after feeding, but it is not a mistake to conclude based on the materials.…”
Section: Methodssupporting
confidence: 59%
“…The similarities and differences of L. paluda recorded from various parts of the world were analyzed. Our study determined that L. paluda, which we determined as the first record from the Fergana Valley region of Uzbekistan, has a longer and wider structure than the leeches from the Samarkand region of Uzbekistan [19]. Likewise, it was also observed that it was larger than the L. paluda species determined from Kazakhstan [15] and other regions in Central Asia [6, 16, and 17].…”
Section: Methodsmentioning
confidence: 68%
See 1 more Smart Citation